Public Opinion on The Postponing the 2024 Election on Twitter Social Media by Online Media of Koran Tempo - Rizqi Fitrianti; April Laksana (IHSA Institute, 2022)
Mass media have a role in the formation of public opinion. Public opinion starts from several factors, one of which is a person's fear of having different opinions in society. For this reason, an individual will monitor the opinion that is formed dominantly in the general public, so that someone will be afraid to express an opinion according to his own expression, but an individual will adjust to become part of the dominant opinion. The problem that will be discussed in this research is the formation of public opinion related to the issue of the postponement of the 2024 Election which is rolling in the Koran Tempo Online Media, so that it becomes a dominant opinion that has an influence on the views and behavior of the audience. This study aims to determine the extent to which Koran Tempo has succeeded in turning the issue of the postponement of the 2024 election into a debatable public opinion. From this research, it is concluded that the media agenda created by online media Koran Tempo with frequency density can shape public opinion of the agenda for postponement of the 2024 election and the extension of the presidential term. Second, the formation of public attitudes and views due to the media exposure of Koran Tempo regarding the postponement of the 2024 election, so that various waves of pros and cons in the social media continue to roll.